High strain rate characterisation of intralaminar fracture toughness of GFRPs for longitudinal tension and compression failure. (15th May 2020) - Catalanotti, G.; Kuhn, P.; Xavier, J.; Koerber, H.
Abstract: The elastic parameters, strengths, and intralaminar fracture toughness are determined for an E-Glass polymer composite material system, statically and at high strain rate, adapting methodologies previously developed by the authors for different carbon composites. Dynamic experiments are conducted using tension and compression Split-Hopkinson Bars (SHBs). A unique set of experimental parameters is obtained, and reported together with the experimental set-up, in order to ensure reproducibility. While in-plane elastic and strength properties were obtained by testing one specimen geometry, intralaminar fracture properties required the testing of different sized notched specimens with scaled geometries. This allowed the use of the size-effect method for the determination of the dynamic R-curve. When comparing these results with those previously obtained for a carbon/epoxy material system, it is observed that the dynamic fracture toughness exhibits a much more significant increase in both tension and compression. The obtained results permit the identification of the softening law at different strain rates, allowing its use in any analytical or numerical strength predictive method.